Biologically Augmented Quadriceps Tendon Autograft With Platelet-Rich Plasma for Anterior Cruciate Ligament Reconstruction - Jorge Chahla, M.D., Ph.D.; Mark E. Cinque, M.D.; Bert R. Mandelbaum, M.D., D.H.L., (hon.) (Arthroscopy Techniques, 2018)
Anterior cruciate ligament (ACL) reconstruction is one of the most common procedures studied in the orthopaedic literature. In this regard, graft preparation is a key factor for successful outcomes. Although current methods to reconstruct the ACL are generally perceived to be successful, recent studies indicate that normal structure and function of the knee are fully restored in less than half of the patients. Therefore, biologically augmenting these scaffolds could provide a potential solution for improving healing times and biomechanical properties of the graft. The purpose of this Technical Note is to describe our preferred technique for an ACL graft preparation (quadriceps tendon) augmented with platelet-rich plasma.